The Effectiveness Of Using Flashcard To Increase Vocabulary At Seven Grade Of MTS Swasta Muhammadiyah 22 Padangsidimpuan - Siregar, Dinda Khairunnisa Panduman; Harahap, Rosni; Mahrani; Sari, Siti Meutia (ETANIC Journal Of English Language Teaching And Applied Linguistics, 2025)
The research’s goal is to know the students ‘skill in vocabulary through Flashcards in learning English. The number of samples of this research was 30 students using the purposive sampling technique of VII-B class. Qualitative research method is applied for this research of the Classroom Action Research (CAR) design in order to know the increasing of the students’ skill in mastering vocabulary through Flashcards. The instrument of the research is a test by giving the multiple-choice items. All of the data are collected and analyzed to get the conclusion as a result of this research. The result of the research showed that the students vocabulary result in pre-test before using flashcard mean score 43.67. It was done three meetings for learning process using flashcard method at the classroom and one meeting for the test of cycle 1. The mean score of the cycle 1 test was 68.67. then, the cycle 2 process was done three meetings for learning process and one meeting for doing the test. Based on the finding the result of cycle 1 mean score was improved and increased, it can be seen from the mean score 81.17. The finding hypothesis is also accepted. Finally, there is the increasing student’s skill towards vocabulary by using flashcard.